SISTEM PENDUKUNG KEPUTUSAN RECRUITMEN KARYAWAN DI TOKO BUKU GRAMEDIA JAMBI - Budiarti, Rike Limia (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2018)
Gramedia Bookstore Jambi is the largest and most comprehensive bookstore in the city of Jambi engaged in retail. In terms of employee recruitment managerial party Gramedia Jambi have difficulty in finding and determine the appropriate new employees accordingly. This makes the recruitment process starting from the processing of new employee data to the determination of employees to be less effective because it still uses estimates and manual assessment so that the recruitment process does not get the right employees. For the recruitment process required enter (input) data that support each other ie data prospective employees, data test results sell products, test interview data then the data will be processed so as to produce output or report test results. While the assessment of employees who will exhaust the contract required employee performance assessment to determine the continuation of employment contracts required enter (input) ie employee data, performance criteria assessment data. In this case a Web-based Management Information System is required. The purpose of writing this script is to create a web-based system especially to facilitate the processing of recruitment data using the programming language HTML, PHP and MySQL as the database in the application Management Information Systems Recruitment Gramedia Jambi. The methodology used in writing this thesis is field research, literature study. The results of the analysis and design of Management Information Systems is expected to provide kemudahnan in data processing and can provide assistance in terms of performance appraisal. For suggestions this application can be developed by adding the necessary processes in the future.